Diseño de objetos virtuales de aprendizaje para promover la autoformación en fundamentos contables aplicados al emprendimiento (2014)
The technologies of Informatic and communications TIC have become a critical success factor for the construction of digital educational resources used widely; however, the perception in terms of satisfaction of users, of this type of virtual courses aimed at accounting fundamentals is significantly negative. Starting from the premise that a course properly structured and developed hould promote self-learning in students who use it. The developers of this investigation work guided by the interest of establishing general begin to know the opinion of experts in accounting issues and that have been users of virtual courses. In addition, this investigation work inquires by tools user greater of worldwide acceptance for the construction of educational resources and suggests the design of a course in accounting basics for students of entrepreneurship that is able to develop the skills required and further promote independent learning.